The use of the mother tongue in the foreign language classroom of the Great Florianópolis (SC) region: a study of state school teachers' perceptions - Moreira, Maria Aparecida Rita (2001)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro de Comunicação e Expressão. Programa de Pós-Graduação em Letras/Inglês e Literatura Correspondente.